Synthesis of a C20-Deoxygenated Spirangien Derivative for Target Identification - Bluhm, Nadine; Kalesse, Markus (Synlett, 2015)
The synthesis of a C20-deoxygenated spirangien derivative is described that allows the incorporation of various affinity labels for target identification of this potent natural product. The synthesis takes advantage of two major building blocks that can be accessed in 8 and 14 steps, respectively. The endgame joins both fragments through a selective aldol reaction and final protecting group manipulations furnish the target molecule.
Keywords: natural product synthesis; spirangien; aldol reaction; target identification